1987
DOI: 10.1149/1.2100725
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Sulfidation of Copper Single Crystals

Abstract: The oxidation of copper single crystals is known to proceed at different rates on different crystal faces. To determine whether this behavior extends to subsequent atmospheric sulfidation as well, we have exposed polycrystalline copper and (100), (110), and (111) single crystals of copper to low concentrations of hydrogen sulfide in high humidity air. For short exposures, all of the single crystals sulfidize much more slowly than does polycrystalline copper. In each case, Cu2S is the predominant sulfur speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 12 publications
(20 reference statements)
0
13
0
Order By: Relevance
“…Despite the beneficial properties of copper, it is well known that it is thermodynamically unstable and readily develops a copper oxide film in the surface after the initial exposure to the environment, which is metallurgically and chemically complex. [1][2][3][4][5] Initially oxygen and water react with a fresh copper surface, forming cuprite Cu 2 O as the main corrosion product. Following the introduction of common pollutants such as SO 2 , NO 2 , Cl, and H 2 S, several different patina compounds form on top of the initial cuprite layer.…”
mentioning
confidence: 99%
“…Despite the beneficial properties of copper, it is well known that it is thermodynamically unstable and readily develops a copper oxide film in the surface after the initial exposure to the environment, which is metallurgically and chemically complex. [1][2][3][4][5] Initially oxygen and water react with a fresh copper surface, forming cuprite Cu 2 O as the main corrosion product. Following the introduction of common pollutants such as SO 2 , NO 2 , Cl, and H 2 S, several different patina compounds form on top of the initial cuprite layer.…”
mentioning
confidence: 99%
“…Pure copper usually has no obvious corrosion tendency, but it will be seriously corroded in Oxygenated water, oxidizing acids and seawater in the marine atmosphere [2][3][4]. Therefore, in recent years, people have improved the corrosion resistance of copper through various surface treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Although many laboratory studies have been made of atmospheric copper corrosion in an environment with a high concentration of corrosive gases, [16][17][18][19][20][21][22] few have focused on corrosion behaviour in an actual environment with a high H 2 S concentration. 23 In the study reported here, we investigated atmospheric corrosion of copper exposed indoors and outdoors in a hot springs area.…”
Section: Introductionmentioning
confidence: 99%